2017
DOI: 10.1162/isec_a_00284
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Hiroshima in Iran: What Americans Really Think about Using Nuclear Weapons and Killing Noncombatants

Abstract: Numerous polls demonstrate that U.S. public approval of President Harry Truman's decision to drop the atomic bombs on Hiroshima and Nagasaki has declined significantly since 1945. Many scholars and political figures argue that this decline constitutes compelling evidence of the emergence of a “nuclear taboo” or that the principle of noncombatant immunity has become a deeply held norm. An original survey experiment, recreating the situation that the United States faced in 1945 using a hypothetical U.S. war with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 33 publications
14
117
4
Order By: Relevance
“…Across all respondents, approval for the nuclear strike against Iranian civilians was 34.2%. This was lower than in the Sagan and Valentino study (9), although still substantial. But, as will be demonstrated below, overall support may be higher or lower depending on the nature of the sample, specific wording of questions, and the real-world conditions at the time of the survey.…”
Section: Survey 1 Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…Across all respondents, approval for the nuclear strike against Iranian civilians was 34.2%. This was lower than in the Sagan and Valentino study (9), although still substantial. But, as will be demonstrated below, overall support may be higher or lower depending on the nature of the sample, specific wording of questions, and the real-world conditions at the time of the survey.…”
Section: Survey 1 Resultscontrasting
confidence: 65%
“…Vengeful tendencies have been found to predict support for wars and assassinations (10)(11)(12)(13)(14)(15)(16) and to be prevalent in the desire to punish transgressors in everyday life as well (17). The strongest attitudinal predictor of vengefulness in warfare has been the degree to which an individual supports the death penalty for persons convicted of murder (16,18), a finding replicated in the Sagan and Valentino study (9).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Second, as Alexander Downes has shown, during the pre-nuclear era governments and militaries often ignored the moral proscription against deliberately targeting civilian populations, usually when their military positions became precarious or in order to achieve victory at the lowest possible cost to themselves (Downes 2008). A recent study by Scott Sagan and Benjamin Valentino found that "The majority of the U.S. public has not internalized either a belief in the nuclear taboo or a strong noncombatant immunity norm" (Sagan and Valentino 2017). These findings call into question the assumption of the just war thinkers that a nuclear war could and would be fought with limited, counterforce strikes.…”
Section: Just War Thinkers Vs Nuclear Pacifists: Summarizing the Debatementioning
confidence: 99%
“…Domestic structures matternational security decision-making in different countries is to a different extent responsive to the public opinion. Furthermore, public opinion is not universally opposed to the nuclear weaponsin fact, the nuclear weapon taboo is quite weakly represented in public opinion (Press, Sagan, & Valentino, 2013;Sagan & Valentino, 2017). This is not to say that norm against the use of nuclear weapons does not exist -Western nuclear weapons states continue to explain the need to keep nuclear weapons, underlining their awareness of the existing norm against their use.…”
Section: Will It Strengthen Norms?mentioning
confidence: 99%